PELATIHAN PENINGKATAN LITERASI DALAM PENGGUNAAN MEDIA PEMBELAJARAN KOMIK DI SDS ANGKASA 4 JAKARTA TIMUR - Eka Septiani; Nur Indah Sari; Indra Martha Rusmana (LPPM Universitas Bina Bangsa, 2021)
Reading skills play an important role in our lives because knowledge is acquired through reading. Therefore, this skill must be mastered by students well from an early age. Unfortunately, in the 21st century, the literacy ability of students has decreased. The general objective of this activity is to use comic-based learning media in order to help improve the literacy culture of students. The specific purpose of this activity is to increase the creativity of teachers in developing learning media, namely comic-based. The benefit of this activity for the school is to produce a comic that can help them improve the literacy movement in their school. The benefit of the activity for teachers is to develop their creativity in producing a work that can improve to literacy of students